2016
DOI: 10.1186/s40781-016-0089-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of season and age at first calving on genetic and phenotypic characteristics of lactation curve parameters in Holstein cows

Abstract: In this research data representing 72,946 primiparous cows from 724 herds with 638,063 total test day records calved between 2001 and 2011. These data were analysed to determine the effect of age at first and season of calving on parameters of the Wood lactation curve. Also, genetic trend of the lactation curve parameters in different calving years were evaluated. The results indicate that the highest rate of atypical lactation curve was related to cows that calved in summer (28.05 %). The maximum phenotypic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 37 publications
6
18
2
3
Order By: Relevance
“…In the same line with the current study, Torshizi [ 25 ] reported that both the feeding schedule and the relative humidity are the critical factors for calving season definition; hot weather seasons have a passive effect on milk characteristics, especially fat yield. As proposed by this author, cows that calved in autumn and winter seasons have average peak milk production more than ones calved in spring and summer seasons.…”
Section: Discussionsupporting
confidence: 88%
“…In the same line with the current study, Torshizi [ 25 ] reported that both the feeding schedule and the relative humidity are the critical factors for calving season definition; hot weather seasons have a passive effect on milk characteristics, especially fat yield. As proposed by this author, cows that calved in autumn and winter seasons have average peak milk production more than ones calved in spring and summer seasons.…”
Section: Discussionsupporting
confidence: 88%
“…The heritability for AFC in this study was close to zero (0.00 ± 0.05). Torshizi (2016) reported a low h 2 value (0.075 ± 0.002) in Iranian Holstein cows. This result differs from what has been previously reported in BON cattle in a study carried out by M-Rocha et al (2012).…”
Section: Results and Discusionmentioning
confidence: 90%
“…In terms of volume, milk losses and gains can be regarded from the perspective of pre-22 months; 22-25 months and post 25 months AFC. At an AFC of less than 22 months, 590-800 kg losses in the first 305 day lactation have been reported by (Elahi Torshizi, 2016) and (Pirlo, 2011). Ettema (2004) included pre-23 months in his study and reports a 320 kg loss in the first lactation: the lower volume lost is most likely because the cows at 22-23 months were included in the calculation.…”
Section: Milk Yieldmentioning
confidence: 95%